Prawne zagadnienia związane z dostępem do zawodu syndyka = Legal issues related to access to profession of curator in bankruptcy - Agata Klimczyk (Kazimierz Wielki University, 2015)
Klimczyk Agata. Prawne zagadnienia związane z dostępem do zawodu syndyka = Legal issues related to access to profession of curator in bankruptcy. Journal of Education, Health and Sport. 2015;5(8):307-310. ISSN 2391-8306. DOI 10.5281/zenodo.28819 http://dx.doi.org/10.5281/zenodo.28819 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A307-310 https://pbn.nauka.gov.pl/works/611539 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-4fcd78eb-6ccb-421d-be28-3b9102c95678 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2015. Revised 21.08.2015. Accepted: 21.08.2015.   Prawne zagadnienia związane z dostępem do zawodu syndyka Legal issues related to access to profession of curator in bankruptcy   Agata Klimczyk Nicolaus Copernicus University in Toruń   Streszczenie          Celem niniejszej pracy jest przedstawienie podstawowych problemów związanych z zdaniami syndyka oraz wymaganiami, które powinna spełniać osoba starająca się o zostanie syndykiem. W pracy posłużono się metodą polegającą na analizie aktów prawnych i fachowej literatury. Główne wnioski autora są związane z akceptacją utrudnień związanych z dostępem do tego zawodu.   Abstract          The main aim of this work is to show main issues related to profession of curator in bankruptcy. And requirement which must meet candidate for this profession. In the work was used special literature and legal regulations. Main conclusion are related to acceptance of requirements related to access to this profession.   Key words: insolvency, curator in bankruptcy, profession, law. Słowa kluczowe: niewypłacalność, syndyk, zawód, prawo.